Summer Bridge Program: Helping Underserved Students Develop Social and Cultural Capital - Simon, Nicolas; Hornung, Rick; Dugan, Kim (Journal of Interdisciplinary Studies in Education, 2022)
Social and cultural capital are critical components of success among college students. In this paper, we examine the creation, accumulation, and distribution of social and cultural capital by and among underserved college students who participated in a summer bridge program at one regional public state university. Using qualitative data from interviews with participants, the analysis highlights the importance of trust, sense of belonging and use of non-cognitive strategies. We argue that in addition to traditional achievement measures such as GPA and test scores, social and cultural capital need to be considered. While quantitative measures often label these students as below benchmarks, this study highlights how social and cultural capital are assets to be nurtured and facilitated.